2002
DOI: 10.1006/rtph.2002.1558
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sensitivity of Children and Adults to Chemical Toxicity

Abstract: Animals can be useful predictors of chemical hazards to humans. Growth and development are compressed into a shorter period in animals, which makes interpretation of animal testing inherently more difficult. However, similar events occur in both humans and laboratory animals and testing that covers the full period of animal development can reasonably be considered an appropriate surrogate for human development. Some have proposed an additional 10-fold factor for the extra protection of children when estimating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(98 citation statements)
references
References 108 publications
2
93
1
2
Order By: Relevance
“…Previous studies that have employed healthy adults as the participant sample have reported smaller effect sizes than those observed here [9] [10]. This differential in effects may be the consequence of general age-related changes in physiological and pharmacological sensitivity that have been reported for a range of drugs and toxins [40]. If this is the case it would offer support to the previously proposed pharmacological mechanism that may underpin the activity of Rosemary aroma [41].…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies that have employed healthy adults as the participant sample have reported smaller effect sizes than those observed here [9] [10]. This differential in effects may be the consequence of general age-related changes in physiological and pharmacological sensitivity that have been reported for a range of drugs and toxins [40]. If this is the case it would offer support to the previously proposed pharmacological mechanism that may underpin the activity of Rosemary aroma [41].…”
Section: Discussionmentioning
confidence: 53%
“…Developmental characteristics of children as a response to their living environment are specific bioaccumulation, absorption, distribution, foetal and transitional perinatal metabolic and detoxifi cation enzymes and kidney clearance (102). Adult values for glomerular fi ltration rate, maximum tubular excretory capacity, and maximum renal concentrating capacity are achieved by the age of 2 years.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The scientific literature shows that children may be more sensitive, equally sensitive or less sensitive to effects from chemical exposures than adults [39]. While children over 6 months of age can be more sensitive than adults to chemical toxicity, in many cases they are less sensitive [40]. Furthermore, Dourson et al [41] concluded that, taking into account relative sensitivities of adults and children and the types and the scope of toxicity test protocols that substances are subjected to, additional uncertainty factors, over and above those traditionally used, are generally not supported for addressing concerns to children greater than 6 months of age.…”
Section: Reproductive and Developmental Toxicity Testingmentioning
confidence: 99%